Mechanisms of the Ping-wei-san plus herbal decoction against Parkinson’s disease: Multiomics analyses - Li, Ding; You, Hong-juan; Hu, Guo-jie; Yao, Ru-yong; Xie, An-mu; Li, Xiao-yuan (Frontiers in Nutrition, 2023)
Parkinson’s disease is a neurodegenerative disorder involving the loss of dopaminergic neurons. Multiple studies implicate the microbiota-gut-brain axis in Parkinson’s disease pathophysiology. Ping-wei-san plus Herbal Decoction, a traditional Chinese medicine composition with beneficial effects in Parkinson’s disease, may have a complex array of actions. Here we sought to determine whether gut microbiota and metabolic pathways are involved in Ping-wei-san plus herbal therapy for Parkinson’s disease and to identify functional pathways to guide research. The model of Parkinson’s disease was induced with rotenone. The Ping-wei-san plus group received the PWP herbal decoction for 90 days, after which all groups were analyzed experimentally. PWP herbal treatment improved motor behaviour and emotional performance, balanced gut microbiota, and benefited dietary metabolism. Tandem Mass Tags mass spectrometry identified many differentially expressed proteins (DEPs) in the substantia nigra and duodenum in the PWP group, and these DEPs were enriched in pathways such as those involving cAMP signalling, glutamatergic synapses, dopaminergic synapses, and ribosome-rich functions in the gut. The PWP group showed increases in tyrosine hydroxylase, recombinant tissue inhibitors of metalloproteinase 3, and nucleotide-binding oligomerization domain,leucine rich repeat and pyrin domain containing proteins 6 in the substantia nigra and decreased parkin, gasdermin D, recombinant tissue inhibitors of metalloproteinase 3, and nucleotide-binding oligomerization domain,leucine rich repeat and pyrin domain containing proteins 6 in the duodenum. In conclusion, this study combined gut microbiota, metabolomics, and proteomics to evaluate the mechanism of action of Ping-wei-san plus on Parkinson’s disease and revealed that PWP herbal treatment modulated gut microbiota, altered metabolite biological pathways, and affected functional pathway protein expression in Parkinson’s disease mice, resulting in therapeutic effects.